Development and testing of a variable-spam morphing wing - Felício, João Miguel Inácio (2015)
The present work focuses on the development and validation of a variable-span morphing wing (VSW) to be fitted to a mini UAV. An electro-mechanical actuation mechanism is developed using a simple rack and pinion system. The wing model is designed with the help of graphical CAD/CAE tools and then a full scale model is built for bench testing the strength, power consumption, deployment time and efficiency. The concepts used on the morphing wing for both fixed and moving wing parts are considered simple and effective. Construction methods and materials were evaluated in order to obtain a system as reliable as possible. Still, in future work the VSW structure can be improved by changing some interface components to achieve a smoother deployment. Also, some work is planned on the design optimization code: implementation of a coupled aero-structural analysis model for simultaneous aerodynamic and structural design optimization problems. Main results: deployment times; efficiency.